Performance of Winter Potato with varied dates of planting under Mid Hills of Meghalaya - Gogoi, Meghna; Ray, Lala I.P. (Indian Journal of Hill Farming, 2019)
The performance of Potato (Solanum tuberosum L.) was assessed under mid hills of Meghalaya during winter season of 2016-17. A field trial was laid out with four different dates of planting, viz. D1- 1st November, D2- 11th November, D3- 21st November and D4- 1st December and replicated thrice. Irrigation was provided with micro irrigation system at respective scheduled dates. Tubers planted on D2 date of sowing showed higher results for number of leaves per plant, leaf area index (LAI), dry matter accumulation (g), number of tubers per plant, weight of tubers per plant (g), tuber yield (t ha-1) and benefit cost ratio over D1, D3 and D4. The highest recorded tuber yield was 15.30 t ha-1 for D2 over other three planting dates. Similarly the maximum field water use efficiency (WUE) was recorded for D2 (56.09 kg ha-1mm-1) and the value of WUE for D1, D3 and D4 are 50.37 kg ha-1mm-1, 49.71 kg ha-1mm-1 and 44.23 kg ha-1mm-1, respectively.